Optimization of biogas as renewable energy from closed anaerobic digestion biomass for palm oil mill effluent at mesophilic temperature - Lee, Hong Chen (Penerbit Universiti Malaysia Perlis, 2010)
Palm oil mill effluent (POME) is a highly polluting wastewater that pollutes the environment if discharged directly due to its high chemical oxygen demand (COD) and biochemical oxygen demand (BOD) concentration. In addition, anthropogenic release of greenhouse gases, especially carbon dioxide (CO2) and methane (CH4) from POME anaerobic degradation process has been recognized as one of the main causes of global warming. Thus, this study aims to discuss the COD removal efficiency, behavior of volatile fatty acid (VFA) and efficiency of biogas production in the suspended closed anaerobic reactor (SCAR) for the treatment of POME wastewater. The operation of this research study was performed by a series of continuous experiments using feed flow-rates of 375 ml/d [run 1], 450 ml/d [run 2], 560 ml/d [run 3], 750 ml/d [run 4], 1125 ml/d [run 5] and 2250 ml/d [run 6] of the wastewater, which correspond to hydraulic retention time (HRTs) of 12, 10, 8, 6, 4 and 2 days, respectively. The duration of the experimental runs 1, 2, 3, 4, 5 and 6 was 27, 15, 11, 18, 14 and 14 days, respectively. The results indicated that the COD removal efficiency and the biogas production rates decreased from 87.08 % to 38.20 % and from 3000 ml biogas/day to 604 ml biogas/day, respectively as HRT decreased. Meantime, the VFA concentration increased from 11569.71 mg CH3COOH/L to 16956.00 mg CH3COOH/L with a decrease in HRT. Moreover, the methane content and the CH4: CO2 fraction decreased from 24.05 % to 10.64 % and from 0.76 to 0.27, respectively with a decrease in HRT whereas the carbon dioxide and hydrogen contents were increased from 31.45 % to 39.63 % and from 4.35 % to 8.15 %, respectively, with a decrease in HRT. These were attributed to variation of HRT that affects the system stability.